Tradisi Anjangsana sebagai Upaya untuk Menjalin Silaturrahmi di MAN 5 Kediri - Iqlima Zahari (Departement of Mathematics Education, 2022)
Anjangsana according to KBBI is a visit to relieve longing; visits (visiting the house of neighbors, relatives, old friends, best friends). The anjangsana tradition in the context of rural communities means visiting fellow residents. The anjangsana tradition is a positive step to build good relationships with anyone because in friendship there is enthusiasm, brotherhood and closeness with one another. Silaturrahmi is connecting love or kinship that desires goodness. This research answers how the anjangsana tradition is carried out by the academic community at MAN 5 Kediri. This research includes qualitative research with a Grounder Theory approach. Data collection uses interviews, observation, documentation. The analysis techniques are data reduction, data presentation, and conclusion drawing (verification). The research results obtained by anjangsana activities are very beneficial for MAN 5 Kediri students, the benefits include: First, students learn to visit each other/stay in touch with their friends. Second, students train in society and organization. Third, reduce students playing outside the home which is not useful. The benefits of anjangsana for teachers/tendik include, firstly, to strengthen ties between teachers and the MAN 5 Kediri academic community. Second, as a medium for motivation and self-muhasabah, because in anjangsana there is tausiyah and evaluation for oneself and the organization. Students and teachers are very enthusiastic about anjangsana activities because they are a medium for friendship between the academic community at MAN 5 Kediri.